Polarizable Nanowire Colloids for Power Free Naked Eye Optical Detection of Electrostatic Surface Charges. Issue 9 (30th September 2016) - Šutka, Andris; Timusk, Martin; Loot, Ardi; Joost, Urmas; Käämbre, Tanel
Abstract : Polarizable visible light absorbing nanowire colloids change their apparent color from vivid to black in presence of electrostatic charge, as the nanowires become aligned in an electric field of electrostatic surface charges. Colloids can be applied for electrostatic‐charge naked‐eye optical detection. This knowledge is important in other fields, e.g., low‐energy colorful display technologies.